2019
DOI: 10.3390/ijms20205192
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Centric Approach Reveals a Novel Glycosyltransferase from the GA A07 Strain of Bacillus thuringiensis Responsible for Catalyzing 15-O-Glycosylation of Ganoderic Acid A

Abstract: Strain GA A07 was identified as an intestinal Bacillus bacterium of zebrafish, which has high efficiency to biotransform the triterpenoid, ganoderic acid A (GAA), into GAA-15-O-β-glucoside. To date, only two known enzymes (BsUGT398 and BsUGT489) of Bacillus subtilis ATCC 6633 strain can biotransform GAA. It is thus worthwhile to identify the responsible genes of strain GA A07 by whole genome sequencing. A complete genome of strain GA A07 was successfully assembled. A phylogenomic analysis revealed the species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The four Bacillus GTs have been considered genetically distinct among the known triterpenoid-catalyzed GTs until now ( Figure 1 ). Previous studies revealed that BsUGT398, BsUGT489, and BtGT_16345 have catalytic specificity toward glycosylating the C-15 hydroxyl group of the GAA triterpenoid [ 16 , 17 ]. In addition, BsGT110 was the first GT that glycosylated the C-26 carboxyl group of the GAA triterpenoid.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The four Bacillus GTs have been considered genetically distinct among the known triterpenoid-catalyzed GTs until now ( Figure 1 ). Previous studies revealed that BsUGT398, BsUGT489, and BtGT_16345 have catalytic specificity toward glycosylating the C-15 hydroxyl group of the GAA triterpenoid [ 16 , 17 ]. In addition, BsGT110 was the first GT that glycosylated the C-26 carboxyl group of the GAA triterpenoid.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, BsUGT489 was found to glycosylate the C-3 hydroxyl group of GAG. Table 1 and Figure 5 summarize the comparative results of the biotransformation of GAA [ 15 , 16 , 17 ] and GAG with the four Bacillus GTs. The main structure of ganoderic acid contains five functional groups that could be modified: the C-3, C-7, C-12, and C-15 hydroxyl groups, and the C-26 carboxyl group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The enzyme is also regioselective toward triterpenoid substrates. BtGT_16345 showed glycosylation activity toward seven flavonoids (apigenin, quercetin, naringenin, resveratrol, genistein, daidzein, and 8-hydroxydaidzein) and two triterpenoids (GAA and antcin K) [11].…”
mentioning
confidence: 99%